Abstract Volume of Tenth Nepal Geological Congress on Geosciences for Sustainable Development and Prosperity, 7 – 8 March 2021, Kathmandu, Nepal (Journal of Nepal Geological Society, 2021)
This is the full volume of the Abstracts from the STenth Nepal Geological Congress on “Geosciences for Sustainable Development and Prosperity”, 7 – 8 March 2021, Kathmandu, NepalJournal of Nepal Geological Society, 2021, Vol. 61 (Sp. Issue)